The dark side of the STEM and how to fight it. Contributions from Digna Couso to the summer school of EduglobalSTEM - Núria Garcia (Universitat Autònoma de Barcelona, 2020)
Over the last few years, STEM education has been gaining momentum from both public institutions and the private sector. Much is said and speculated about the hidden interests that may be behind this impulse, dark interests, which aim to perpetuate the geopolitical and social-labour status quo. This article explains how Dr. Digna Couso, during her talk at the First EduglobalSTEM Summer School, provided insight into the dark side of STEM education, and told us the best ways to fight it: to conquer it from a global justice and diversity approach to values. She also spoke to us about the importance of knowing the biases operating in STEM education, what consequences they may have, and what tools are available to reverse those biases.